Transforming Islamic Higher Education Toward World-Class Universities: An Integrated Model of Islamization, Digitalization, and Internationalization - Nasrul Syakur Chaniago; Amiruddin Siahaan; Abdurrahman Abdurrahman (JURNAL AL-TANZIM, 2026)
This study aims to analyze the process of institutional innovation in transforming an Islamic university into a world-class institution through the integration of Islamization, digitalization, and internationalization. A qualitative approach with a naturalistic case study design was employed at an Islamic university. Data were collected through observation, semi-structured interviews, and document analysis, and subsequently analyzed using an interactive model comprising data condensation, data display, and conclusion drawing and verification. The findings indicate that institutional innovation is a continuous governance transformation process built upon three interacting pillars. Islamization, through the Wahdatul 'Ulum paradigm, strengthens epistemological integration and establishes academic and institutional identity. Digitalization drives governance modernization, enhances academic services, and facilitates data-driven decision-making. Meanwhile, internationalization bolsters institutional capacity through the development of networks and sustained global academic collaborations. These three dimensions operate synergistically, supported by transformational leadership, quality assurance systems, human resource development, and integrated governance. The study concludes that transforming into a world-class Islamic university requires balancing Islamic identity, technological innovation, and global engagement. It contributes an integrated institutional transformation model and offers strategic implications for enhancing the competitiveness and academic excellence of Islamic higher education institutions.